In this worksheet, you must multiply out two algebraic brackets.

**Method**

When we multiply out brackets we split the first bracket and multiply each term by the second bracket, as follows:

(a + b)(c) = a(c) + b(c)

(a - b)(c) = a(c) - b(c)

(**Remember - when we write a(c), we could also write this as a x (c)**

So that's with one value in the second bracket, but what if we had two?

1) (a + b)(c + d) = a(c + d) + b(c + d)

= ac + ad + bc + bd

Now we have the basics we're going to apply this to some more complex maths. Remember, the process is exactly the same, even if it looks a bit more intimidating.

**Examples**

**(x + 3)(x - 6)** = x(x - 6) + 3(x - 6) = x^{2 }- 6x + 3x - 18

= **x ^{2 }- 3x - 18 **

**(2x - 1)**= (2x - 1)(2x - 1) = 2x(2x - 1) - 1(2x - 1) = 4x

^{2}^{2 }- 2x - 2x + 1

=

**4x**

^{2 }- 4x + 1